The Psychometric Characteristics of a scale for parental emotional blackmail - Alshamsan, Lamia Ibrahim; Alrebdi, Sufyan Ibrahim (Journal of Educational and Psychological Sciences, 2023)
This study aimed to design a scale for parental emotional blackmail and verify its psychometric characteristics. Based on the objective of the study, the descriptive method was deemed appropriate and utilized. The sample consisted of 104 high school students in Buraydah city, comprising 45 males and 59 females. The psychometric properties of the scale were verification using applicable statistical analyses to arrive to the final version of the scale. The exploratory factor analysis revealed saturation in the factorial structure of the parental emotional blackmail scale in two factors: (fear and guilt, obligation). Internal consistency was also calculated using the Pearson correlation coefficient, where the correlation coefficients of the items of the scale and the total score of the dimension to which the items belong were all positive correlation coefficients and statistically significant at the level of 0.01, which confirms consistency and homogeneity of the items of each dimension. The reliability of the scale and its sub- dimensions was verified using the Cronbach Alpha coefficient, reliability coefficient according to Cronbach Alpha equation of 0.939 for the entire scale. The results showed that the scale and its sub- dimensions had high and statistically acceptable validity and reliability coefficients.